2002
DOI: 10.1046/j.1463-6395.2002.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic anatomy and ultrastructure of the digestive system of Natatolana obtusata (Vanhöffen, 1914) (Crustacea, Isopoda)

Abstract: The scavenging cirolanid isopod Natatolana obtusata was caught using primarily meat‐baited traps at a station in the Weddell Sea at Kap Norvegica. The hindguts of most specimens were densely stuffed with meat from the traps. The anatomy and the ultrastructure of different sections of the digestive system are described. The large and extremely expandable mouth opens into a short oesophagus which extends posteriorly into a small stomach. Lateralia and primary filter can be observed directly when the mouth openin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
1
8
0
1
Order By: Relevance
“…This strategy, and scavenging, as seen in Cirolanidae, would seem to be the plesiomorphic strategy within this clade. Some species of Natatolana are scavengers and will enter baited traps (Arntz and Gutt 1999;Marsden 1999;Storch et al 2002). Cirolanid diversity is higher in tropical than cooler regions (Bruce 1986;Keable 1995) and correlates with a more diverse food supply, exemplified by the diversity of a typical food source: fishes.…”
Section: Radiation Ecology and Biogeographymentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy, and scavenging, as seen in Cirolanidae, would seem to be the plesiomorphic strategy within this clade. Some species of Natatolana are scavengers and will enter baited traps (Arntz and Gutt 1999;Marsden 1999;Storch et al 2002). Cirolanid diversity is higher in tropical than cooler regions (Bruce 1986;Keable 1995) and correlates with a more diverse food supply, exemplified by the diversity of a typical food source: fishes.…”
Section: Radiation Ecology and Biogeographymentioning
confidence: 99%
“…This is not to say that a few scavenging species do not reach high densities in cooler waters. Seven species of Natatolana occur in the Southern Ocean (Storch et al 2002). Only 18% of 429 species of Cirolanidae live at depths greater than 200 m (Kensley et al 1996).…”
Section: Radiation Ecology and Biogeographymentioning
confidence: 99%
“…Apical membranes of hepatopancreatic cells are lined with densely packed microvilli, a feature shown to be present in other isopod species [27][28][29]. Large nuclei are ovoid in shape and lacking any projections as those seen N. obtusata [27] or amphibious isopod Ligia italica under starvation [30]. Although some cells appeared to have higher amount of heterochromatin, indicative of lower gene expression and by extension lower overall activity, it was shown that in L. italica part of hepatopancreatic cells were euchromatic, while others had higher amount of heterochromatin [29].…”
Section: Discussionmentioning
confidence: 78%
“…However, it does not seem to be lined with cuticle as seen in some other species of isopods [26] or at least it is not as prominent as in other species. Most of the cell nuclei appeared ovoid or round, with no or only small protrusions compared to nuclei seen in free-living isopod Notatolana obtusata [27]. Moreover, majority of cell nuclei were euchromatic, indicative of active gene expression.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation